Exploring the Frequency, Intensity, and Duration of Loneliness: A Latent Class Analysis of Data from the BBC Loneliness Experiment - Pamela Qualter (MDPI AG, 2021)
Almost all measures of loneliness have been developed without discussing how to best conceptualize and assess the severity of loneliness. In the current study, we adapted the four-item UCLA, so that it continued to measure frequency of loneliness, but also assessed intensity and duration, providing a measure of other aspects of loneliness severity. Using data from participants resident in the UK who completed the BBC Loneliness Experiment (N = 36,767; F = 69.6%) and Latent Class Profile Analyses, we identified four groups of people who scored high on loneliness on at least one of the three severity measures. Duration of loneliness often over months or years seemed to be particularly important in distinguishing groups. Further, group membership was predicted by important demographic and psychological variables. We discuss the findings in terms of implications for research and practice. We highlight the need to explore these profiles longitudinally to investigate how membership predicts later mental and physical health, and well-being.